Implementation of pipelined data encryption standard (DES) using altera CPLD - Teo, Pock Chueng; Yusoff, Z. M.; Sha'ameri, Ahmad Zuri (2000)
The paper presents a pipelined data encryption standard (DES) architecture design implemented in Altera CPLD. The architecture contains three main parts, DES module, pipeline module and control unit module. A four-segment pipeline is used in this architecture to burst the throughput of the DES. Although the processing time for a single encryption operation is still the same; but with more encryption operations, this pipelined DES can increase significantly the throughput. Altera Hardware Description Language (AHDL) is used to implement the pipelined DES design